ADDRESSING TAX AVOIDANCE THROUGH OECD BEPS POLICY: AN EVALUATION - Loso Judijanto; M. Amin Fatulloh (Adisam Publisher, 2025)
BEPS consists of a series of measures created to close loopholes in international tax regulations that allow companies to channel their profits to jurisdictions with low or zero tax rates. The study conducted in this research uses the literature study method. The results show that the BEPS policy has successfully improved transparency and accountability in multinational companies' tax reporting. It strengthens transfer pricing rules, introduces country-by-country (CbC) reporting, and implements a multilateral framework to facilitate cooperation between countries in addressing tax issues. Nonetheless, implementation challenges remain, such as the need for companies to adjust their business structure and operations, as well as the importance of consistent coordination between jurisdictions in implementing this policy.